Compositional Meaning Represented in Indonesian EFL Learners PowerPoint Slides: A Multimodal Viewpoint - Asri Ainun Nisa; Yesi Dambaresya; Siti Nuraisyiah Fauziah (Siliwangi University, 2021)
A proper layout is one of the essential fragments of PowerPoint’s slides. Due to it is one of instruments that needed to display graphs, thin data-density, chartjunk, encoded legends, etc. Therefore, to achieve ideal PowerPoint’s layout, the analysis of compositional meaning is necessary. Compositional meaning consists of information values, salience, framing, based on theoretical frame work which is in accordance with the applicable provisions of color selection, layout, size, positioning must be relevant. The method of this research is qualitative descriptive analysis technique by using the concept of Kress and van Leeuwen (2006) focusing on compositional meaning represented in Indonesian EFL learners PowerPoint slides. The result revealed that the designers of the PowerPoint used the bright color that it clearly differ subheading of the layout. Additionally, the text was positioned properly by placing the priority text on the top part of slide then the less important text was placed in the bottom part. Unfortunately, the designers made the text tone were almost the same tone with the background of the slides. Through the analysis of compositional meaning, it can be used as the rules for students in making PowerPoint.